DIAGNOSTICS AND TREATMENT OF EXCRETORY DEFICIENCY OF PANCREAS IN CHILDREN - S.V. Bel’mer; T.V. Gasilina (Вопросы современной педиатрии, 2009)
Excretory pancreatic insufficiency is relatively frequent pathology in pediatric and therapeutic practice. It can be divided to primary and secondary, inborn and acquired, absolute and relative one. The causes of primary pancreatic insufficiency are agenesia or hypoplasia of pancreas, cystic fibrosis, Shwachman–Diamond syndrome. Secondary excretory pancreatic insufficiency can be caused by resection of pancreas, pancreatitis, pathology of mucous tunic of small intestine, abnormality of antitrypsinactivation with enterokinase deficiency, inactivation of enzymes by acid of duodenal contents in the presence of gastric hyper secretion and others. Excretory pancreatic deficiency has determined clinical signs and can be relatively easily diagnosed by simple laboratory methods: coprogramm and detection of elastase 1 in stool. The ways of its correction are determined by causes of disease, but modern high-active pancreatic enzymes medications must be necessary component of treatment in all cases. Key words: children, pancreatic insufficiency, celiac disease, pancreatic enzymes medications. (Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(2):114-118)